Terrace and semi-detached house renovation compliance with building control regulations in Malaysia - Mohamed Sabri, Bibi Khairani (2018)
Poor compliance to regulation is a common phenomenon among renovated terraced and semi-detached houses in Malaysia. This study aimed to explore the constraints to comply with current regulation in the context of urban housing in Malaysia. It qualitatively evaluates the responses of house owners to comply with the regulation’s requirements and procedures. In addition, the study also obtained feedbacks from the local authorities on the enforcement of the regulation. A total of twenty participants who are house owners in Hulu Langat District and in Putrajaya voluntarily took part in this study. Sixteen participants were from Hulu Langat District while four were from Putrajaya. Those participants from the Hulu Langat District had been involved in illegally renovating their houses. The study investigated the psychological, social, and economic constraints. The highest intensity of constraint is the psychological constraint. The source of the psychological constraint are incapacity to comply to legal procedures, the reverse effect of enforcement, contradicting views on the requirements of building setbacks, the desire to achieve house owners’ dreams, feeling not guilty, and ignorant towards the regulation. Meanwhile, visual influence of the illegally renovated houses and contractors’ advices are the major sources of social constraints. Unaffordability to buy new houses, limited available area, and safeguarding investments were noted as the economic constraints. The also study found that a prerequisite to encourage compliance involving individual taste, preference, and image is the shared values between the regulatory bodies and the regulated entities.A model is proposed for curbing illegal renovation and enhancing compliance .The findings may contribute to improving the current legal framework on house renovation through a new approach in formulating a development control regulation that ensures a quality living environment and wellbeing.